EFEKTIVITAS PELATIHAN LIFE SKILL TERHADAP PENGETAHUAN DAN SIKAP TENTANG KESEHATAN REPRODUKSI REMAJA - Winarti, Eko; Anggi Umbu Pingge, Yusti; Alimansur, Moh; Agung Mirasa, Yudied (Akademi Keperawatan Dharma Husada Kediri, 2024)
The level of knowledge of adolescents regarding reproductive health in Indonesia is still relatively low. Survey results show that many teenagers do not understand the function of reproductive organs, the risk of sexually transmitted diseases, and the importance of family planning. This research aims to determine the effectiveness of life skills training on knowledge and attitudes about adolescent reproductive health. The type of research used in this research uses quantitative methods with a pre-experimental design with a one-group pretest post test design. The population in this study were all teenagers in SMK